2013
DOI: 10.1002/adfm.201303214
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor Composites: Strategies for Enhancing Charge Carrier Separation to Improve Photocatalytic Activity

Abstract: The formation of semiconductor composites comprising multicomponent or multiphase heterojunctions is a very effective strategy to design highly active photocatalyst systems. This review summarizes the recent strategies to develop such composites, and highlights the most recent developments in the field. After a general introduction into the different strategies to improve photocatalytic activity through formation of heterojunctions, the three different types of heterojunctions are introduced in detail, followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
613
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 1,412 publications
(635 citation statements)
references
References 344 publications
12
613
0
10
Order By: Relevance
“…Photoexcited electrons are transferred from CB(B) to CB(A) and this transfer can occur directly between semiconductors due to favorable energetics of the relative positions of CBs, or due to band bending at the interface inducing and internal electric field. Whereas, holes are transferred simultaneously from VB(A) to VB(B) and as a result photogenerated electrons and holes are separated from each other, reducing the recombination probability and increasing the lifetimes of the charge carriers [71]. Both copper oxides, especially Cu2O, are very promising semiconductors for photocatalytic hydrogen production [72][73][74][75].…”
Section: Metallic Copper-plasmonic Photocatalysismentioning
confidence: 99%
“…Photoexcited electrons are transferred from CB(B) to CB(A) and this transfer can occur directly between semiconductors due to favorable energetics of the relative positions of CBs, or due to band bending at the interface inducing and internal electric field. Whereas, holes are transferred simultaneously from VB(A) to VB(B) and as a result photogenerated electrons and holes are separated from each other, reducing the recombination probability and increasing the lifetimes of the charge carriers [71]. Both copper oxides, especially Cu2O, are very promising semiconductors for photocatalytic hydrogen production [72][73][74][75].…”
Section: Metallic Copper-plasmonic Photocatalysismentioning
confidence: 99%
“…Although an impressive solar-to-hydrogen conversion efficiency of 12.4% has been demonstrated using GaAs and p-GaInP 2 in acidic medium, such high performance cannot be sustained due to instability of the photoelectrode material, which undergoes photocorrosion under operating conditions 13 . Previously much of the research has been focused on enhancing light absorption through bandgap engineering 14 , the detrimental effect of unbalanced charge carrier extraction/collection on the efficiency of the four electron-hole water-splitting reaction has remained largely unexplored 15,16 .…”
mentioning
confidence: 99%
“…22,28 Therefore, TiO 2 with fewer defect leads to increasing lifetime of charge carriers, and consequently more separated electrons and holes can migrate to the photocatalyst surface that are beneficial for reduction and oxidation processes in the decomposition of MO. 4,19,[29][30][31] In our previous study, 32 although it cannot be observed directly in XRD, the asprepared (without calcination) TiO 2 with fewer ALD cycles has a lower degree of local order, on the contrary more ALD cycles leading to an improvement of the degree of local order. This phenomenon has also been noticed in previous studies carried out by Alekhin et al 33 and Moret et al 34 In the transformation from amorphous tocrystalline by calcination, the TiO 2 with lower degree of local order leds to be transformed into crystallized TiO 2 with lower degree of crystallinity and conversely, the TiO 2 amorphous with higher degree of local order is able to be transformed into TiO 2 crystalline with higher degree of crystallinity as indicated by the intensity of (101) peak in XRD (Fig.…”
Section: Resultsmentioning
confidence: 75%